The impacts of corporate social responsibility, service quality, and transparency on relationship quality and customer loyalty in the hotel industry - Sung-Bum Kim; Dae-Young Kim (Asian Journal of Sustainability and Social Responsibility (AJSSR), 2016)
The purpose of this study was to test how potential customers' perceptions of a hotel's corporate social responsibility activities, service quality, and transparency affect relationship quality constructs such as trust, satisfaction, and customer loyalty. Our research design consisted of utilizing a convenience survey of 487American potential hotel customers. We then followed a two-step approach, projecting a measurement model and then analyzing a structural model to test the theoretical relationships between the constructs. The following findings within the context of U.S. hotels show: Corporate social responsibility and reputation had positive relationships with trust and satisfaction, while service quality had a direct effect on customer loyalty. In addition, transparency had a significant influence on customer trust. Customer trust had a significantly positive influence on customer loyalty. The influence of satisfaction on customer loyalty is mediated by trust. This research will contribute to scholarly and managerial debates.
Keywords: 650; Customer loyalty; Corporate social responsibility; Corporate reputation; Relationship quality; Service quality; Transparency